Ion-acoustic wave activity in m = 0 helicon plasmas - Shamrai, K.P.; Virko, V.F.; Slobodyan, V.M.; Virko, Yu.V.; Kirichenko, G.S. (Вопросы атомной науки и техники, 2006)
The results of experimental and theoretical study of low-frequency (LF) wave activity in a helicon plasma and in
an inductively coupled magnetized plasma are presented. This activity is shown to relate to ion-acoustic (IA) waves
whose spectra can be either noise and continuous, or spiky, or combined. The origin of activity is ascertained from
correlative measurements of wave characteristics, stationary plasma parameters, and plasma diamagnetic response.
Various driving mechanisms of the IA waves are discussed. Представлены результаты экспериментальных и теоретических исследований низкочастотной (НЧ) волновой активности в геликонной плазме и в индуктивно связанной замагниченной плазме. Эта активность показана относительно ионно-звуковых (ИЗ) волн, спектр которых может быть как шумовой и непрерывный, так и спайки или комбинированный. Природа активности устанавливалась из корреляционных измерений волновых характеристик, стационарных плазменных параметров и плазменного диамагнитного отклика. Обсуждаются различные механизмы возникновения ИЗ волн. Представлені результати експериментальних та теоретичних досліджень низькочастотної (НЧ) хвильової активності у геліконній плазмі та в індуктивно зв’язаній замагніченій плазмі. Ця активність показана відносно іонно-звукових (ІЗ) хвиль, спектр котрих може бути як шумовим і неперервним, так і спайки або комбінований. Природа активності встановлювалась із кореляційних вимірювань хвилевих характеристик, стаціонарних плазмових параметрів та плазмового діамагнітного відгуку. Обговорюються різні механізми виникнення ІЗ хвиль.